Editorial - RATHORE, GAURAV (Journal of the Inland Fisheries Society of India, 2026)
World Health Organization (WHO) has called Antimicrobial Resistance (AMR) as one of the most important public health threats of the 21st century. Antimicrobial resistance (AMR) has got importance because microorganisms are developing resistance to most of the lifesaving drugs. In future, very few drugs would be left for treatment of infectious diseases. The spread of AMR in health care facilities and in food production sectors is a cause of concern. Therefore, many international organizations like the Food and Agriculture Organization of the United Nations (FAO), the World Organization for Animal Health (OIE), and WHO have realized the importance of AMR globally and are addressing AMR in different sectors under an umbrella of “One Health”.